Synthesis, characterization and OFET property of four diaminouracil bridged novel ball-type phthalocyanines - Yazici, Aysegul; Avci, Ayse; Altindal, Ahmet; Salih, Bekir; Bekaroglu, Ozer (WORLD SCI PUBL CO INC, 2018)
New ball-type metallobisphthalocyanines 2 (Co2Pc2) and 3 (Zn2Pc2) were synthesized from the corresponding 4,4 '-[(5,6-diaminopyrimidine-2,4-diyl)bis(oxy)] diphytalonitril 1, which can be obtained by a nucleophilic displacement reaction of 4-nitrophthalonitrile with 5,6-diaminouracil sulfate. Characterization of novel compounds was performed by UV-vis, FT-IR, H-1-NMR, MALDI-TOF mass spectroscopy and elemental analysis. Organic field effect transistor devices (OFETs) with top gate structure were fabricated using these novel compounds as the active material. The devices were characterized by means of their output and transfer characteristics, and it was found that these OFET devices exhibit p-type behavior. When compared with the 2-based device, the OFET with 3 showed higher field effect mobility and larger on/of current ratio.
Keywords: ball-type phthalocyanines; homodinuclear; field effect; threshold voltage; OFET; FIELD-EFFECT-TRANSISTORS; GAS-SENSING PROPERTIES; THIN-FILM TRANSISTORS; HETERO-DINUCLEAR PHTHALOCYANINES; DOUBLE-DECKER LU(III); ELECTROCHEMICAL PROPERTIES; ELECTROCATALYTIC PROPERTIES; ELECTRICAL-PROPERTIES; ZINC-PHTHALOCYANINE; METALLOPHTHALOCYANINES; Chemistry